Evaluation of Two Bryophytes (Funaria hygrometrica and Polytrichum commune) as a Source of Natural Antioxidant - Hanif, Uzma; Ahsan Ali, Hafiz; Shahwar, Durre; Farid, Sidra; Ishtiaq, Saiqa (Asian Journal of Chemistry, 2014)
Extraction of two Bryophyte plants i.e. Funaria hygrometrica and Polytrichum commune was done through methanol in order of their increasing polarity using Soxhlet apparatus. Total phenolic contents were determined with Folin-Ciocalteu reagent which ranged from 30.5 to 547 mg GAE/g of extract. Polytrichum showed significant but slightly less phenolics contents while that of Funaria showed the high phenolic contents having a value of 1630 for Funaria and 975 for that of Polytrichum. Antioxidant activities of these extracts were evaluated through DPPH• radical scavenging, Ferric thiocyanate method, ABTS•+ Assay, FRAP Assay, Superoxide Anion Radical Scavenging Activity, Total phenolics and total flavonoids determination assay, Metal chelating activity, metal chelating effect and ferric thiocyanate (FTC) methods. In terms of TEAC values the extracts of Funaria and Polytrichum had the TEAC value as 97.5 and 71.06. The results of DPPH assay showed that Funaria and Polytrichum showed least IC50 values, hence they have a greater potential. The methanolic extract of Polytrichum showed a very high concentration of flavonoids, 3636.36 of Polytrichum while the other plant sample (Funaria) contained significant but slightly less quantities of flavonoids as 1751.8.